PENDAMPINGAN PENGGUNAAN PERANGKAT BERBASIS IT DALAM DEEP LEARNING BAGI GURU DI SEKOLAH DASAR - Feny Rita Fiantika; Dian Kusmaharti; Arif Mahya Fanny; Susilo Hadi (Universitas PGRI Adi Buana Surabaya, 2025)
The purpose of this community service was to provide training on the use of digital media for learning for elementary school teachers. This activity took place at SDN Klantingsari 1 Tarik, attended by representatives of elementary school teachers from the Tarik sub-district. Teachers received training on Olabs digital learning media for elementary school teachers. The results showed a 50% increase in teacher competency in using Olabs digital learning media.